THE EFFECT OF RADON AND GEOMAGNETIC FIELD ON BIO-SYSTEMS: THE EFFECT OF RADON AND GEOMAGNETIC FIELD ON BIO-SYSTEMS - Adeishvili, Teimuraz; Alexandrov, Aleksandr; Kikalishvili, Khatuna; Zhvitiashvili, Tengiz; Davarashvili, Khatuna (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper deals with the processes of the effects of the radioactive gas radon and geomagnetic disturbance (occurring during magnetic hurricanes) on bio-systems.